Nuclear charge densities in spherical and deformed nuclei: Toward precise calculations of charge radii - Reinhard, Paul-Gerhard; Nazarewicz, Witold (Physical Review C - Nuclear Physics, 2021)
Background: Precise measurements of atomic transitions affected by electron-nucleus hyperfine interactions offer sensitivity to explore basic properties of the atomic nucleus and study fundamental symmetries, including the search for new physics beyond the standard model of particle physics. In particular, such measurements, augmented by atomic and nuclear calculations, will enable extraction of the higher-order radial moments of the charge-density distribution in spherical and deformed nuclei. The new data impose higher precision requirements on a theoretical description.
CRIS-Team WoS Importer:2021-06-18